INKONSISTENSI TEC GIM DARI DATA GNSS SEBAGAI PREKURSOR GEMPABUMI DI WILAYAH MALUKU UTARA TAHUN 2019 - Bambang Sunardi; Supriyanto Rohadi; Sulastri Sulastri; Rahmat Setyo Yuliatmoko (Elipsoida : Jurnal Geodesi dan Geomatika, 2020)
Currently, the GNSS has grown rapidly and is widely applied for commercial and research purposes, one of which is an earthquake precursor. Precursor detection of major earthquakes using TEC in the ionosphere has recently become a promising method. This paper focuses on investigating TEC inconsistencies before major earthquakes in the North Maluku region during 2019. Earthquake data refers to the U.S. Geological Survey, while the TEC data comes from GIM which comes from international GNSS. TEC anomaly was observed by applying the TEC correlation method near the epicenter of the earthquake to obtain the TEC inconsistency index. The TEC anomaly classification is decided when the inconsistency index is outside a defined threshold. The Dst index in the same time frame is used to analyze TEC inconsistencies due to geomagnetic storms. The results of research on the January 7, 2019 Mw 6.6 earthquake, the July, 7 2019 Mw 6.9 earthquake, the July 14, 2019 Mw 7.2 earthquake, and the November 14, 2019 Mw7.1 earthquake showed TEC inconsistency 29 to 1 day before the mainshock. Referring to these results, investigations of TEC inconsistencies prior to the major earthquake can be continuously developed until they reach the expected success rate